Effect of vaccination on the apparent prevalence of bovine brucellosis in the state of Tocantins, Brazil - Vendrame, Fabiano Benitez; Barbosa, Regina Gonçalves; Ferreira, Fernando; Amaku, Marcos; Dias, Ricardo Augusto; Grisi-Filho, José Henrique Hildebrand; Bryan, Marcos Heinemann; Gonçalves, Vitor Salvador Picão; Baquero, Oswaldo Santos; Ferreira Neto, José Soares (Semina: Ciências Agrárias, 2021)
A cross-sectional study on the epidemiological situation of bovine brucellosis was carried out in the state of Tocantins to evaluate the effectiveness of its vaccination program. The state was divided into five regions, and a predetermined number of farms was randomly selected in each one. Females aged 24 months or older were randomly selected in each farm and diagnosed with brucellosis by serial serology (AAT and 2-ME). A total of 6,846 animals from 756 farms were examined. The prevalence of seropositive herds in the state was 6.42% [CI95%: 4.76-8.62], and the prevalence of seropositive animals was 2.21% [CI95%: 1.05-4.01]. The prevalence of seropositive herds was homogeneously distributed among regions. The 2002/2003 study estimated the prevalence of seropositive herds in the state to be 21.22% [CI95%: 19.33-23.11]. In conclusion, the vaccination program implemented in Tocantins, reaching vaccination coverage above 70% as of 2010, significantly reduced the prevalence of seropositive herds. Thus, continuing the vaccination program in the state is recommended, preferably increasing the quality of the processes involved, from commercialization to inoculation in animals, since immunization remains the most effective means to reduce the prevalence of brucellosis. In addition, animal replacement remains a major risk factor for bovine brucellosis in Tocantins since 20022003; therefore, the state must implement a strong health education program explaining to farmers the importance of testing animals for brucellosis before introducing them into their herds.